Patterns of recurrence following selective intraoperative radiofrequency ablation as an adjunct to hepatic resection for colorectal liver metastases. Issue 6 (25th June 2014) - Eltawil, Karim M.; Boame, Nana; Mimeault, Richard; Shabana, Wael; Balaa, Fady K.; Jonker, Derek J.; Asmis, Tim R.; Martel, Guillaume
Abstract Background and Objectives The purpose of this study was to analyze the patterns of recurrence following intraoperative radiofrequency ablation (RFA) combined with hepatic resection for patients with colorectal liver metastases (CLM). Methods Patients undergoing liver resection (with or without RFA) for CLM were examined. Rates and patterns of disease recurrence, as well as overall survival were assessed using Kaplan–Meier and Cox analyses. Results A total of 174 patients underwent liver resection for CLM (150 without and 24 with intraoperative RFA). RFA was used to treat 41 tumors (median 1.6 cm). The 3‐year overall survival was 65.5% and 61.4% (adjusted HR 1.02, 95% CI 0.55–1.88). Median recurrence‐free survival was 7.4 versus 12.7 months with RFA versus non‐RFA, respectively (adjusted HR 1.51, 95% CI 0.94–4.42). On multivariate analysis, neither survival nor recurrence‐free survival was significantly associated with RFA. In total, there were two RFA ablation zone local failures. An ablation site recurrence was the sole site in one patient (4.2%). Conclusion RFA was used as an adjunct to resection in patients with greater disease burden. Despite this, RFA was not significantly associated with a higher risk of local failure and was not associated with worse survival, when compared with liver resection alone. J. Surg. Oncol. 2014 110:734–738. © 2014 Wiley Periodicals, Inc.